2014
DOI: 10.1007/s00114-014-1185-z
|View full text |Cite
|
Sign up to set email alerts
|

Honey loading for pollen collection: regulation of crop content in honeybee pollen foragers on leaving hive

Abstract: Before foraging honeybees leave the hive, each bee loads its crop with some amount of honey "fuel" depending on the distance to the food source and foraging experience. For pollen collection, there is evidence that foragers carry additional honey as "glue" to build pollen loads. This study examines whether pollen foragers of the European honeybee Apis mellifera regulate the size of the crop load according to food-source distances upon leaving the hive and how foraging experience affects load regulation. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Some of the honey at departure is used as fuel for flight (Beutler 1950;Gmeinbauer and Crailsheim 1993). This behavior is well described in the honeybee Apis mellifera (Parker 1926;Beutler 1950;Hodges 1952;Harano et al 2013Harano et al , 2014 and is suggested in stingless bees (Leonhardt et al 2007).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Some of the honey at departure is used as fuel for flight (Beutler 1950;Gmeinbauer and Crailsheim 1993). This behavior is well described in the honeybee Apis mellifera (Parker 1926;Beutler 1950;Hodges 1952;Harano et al 2013Harano et al , 2014 and is suggested in stingless bees (Leonhardt et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…We used the same methods and procedures as in previous studies (Harano et al 2013(Harano et al , 2014 unless otherwise stated. Briefly, waggle dancers and their followers were classified by the size of pollen load presented by dancers and the amount of honey at departure was compared among groups with a different size of pollen load.…”
Section: Measurements Of Crop Content At Departurementioning
confidence: 99%
See 3 more Smart Citations